Mixed Convective-Radiative Dissipative Magnetized Micropolar Nanofluid Flow over a Stretching Surface in Porous Media with Double Stratification and Chemical Reaction Effects: ADM-Padé Computation. (14th February 2022) - Pattnaik, P. K.; Bhatti, M. M.; Mishra, S. R.; Abbas, Munawwar Ali; Bég, O. Anwar
Abstract : The present study deals with the electrically conducting micropolar nanofluid flow from a vertical stretching surface adjacent to a porous medium under a transverse magnetic field. Eringen's micropolar model is deployed for non-Newtonian characteristics and the Buongiorno nanofluid model employed for nanoscale effects (thermophoresis and Brownian motion). The model includes double stratification (thermal and solutal) and also chemical reaction effects, heat source, and viscous dissipation. Darcy's model is employed for the porous medium and a Rosseland diffusion flux approximation for nonlinear thermal radiation. The nonlinear governing partial differential conservation equations are rendered into nonlinear ordinary differential equations via relevant transformations. An innovative semi-numerical methodology combining the Adomian decomposition method (ADM) with Padé approximants and known as ADM-Padé is deployed to solve the emerging nonlinear ordinary differential boundary value problem with appropriate wall and free stream conditions in MATLAB software. A detailed parametric study of the influence of key parameters on stream function, velocity, microrotation (angular velocity), temperature, and nanoparticle concentration profiles is conducted. Furthermore, skin friction coefficient, wall couple stress coefficient, Nusselt number, and Sherwood number are displayed in tables. The validation of both numerical techniques used, i.e., ADM and ADM-Padé, against a conventional numerical 4 th order Runge–Kutta method is also included and significant acceleration in convergence of solutions achieved with the ADM-Padé approach. The flow is decelerated with greater buoyancy ratio parameter whereas microrotation (angular velocity) is enhanced. Increasing thermal and solutal stratification suppresses microrotation. Concentration magnitudes are boosted with greater chemical reaction parameter and Lewis number. Temperatures are significantly enhanced with radiative parameter. Increasing Brownian motion parameter depletes concentration values. The study finds applications in thermomagnetic coating processes involving nanomaterials with microstructural characteristics.